La serie nombrable: Una aproximación a Corpus (1992) de Jean-Luc Nancy desde la lectura de Flores (2001) de Mario Bellatin (De la Crítica, 2023)
With the work of Mario Bellatin Flores (2001), the way of thinking about the body is addressed as cast zone that are often not communicable but together form a whole, a Corpus (1992) in the name of Jean-Luc Nancy. This means that when thinking of the notion of the body as a matter of meaning that admits a radical otherness that recreates, recomposes, conditions and limits it, it is concluded that the body has no borders and, therefore, it does not have a unity because it opens up to experimentation becoming an ever-changing, a nameable series of bodies that metamorphose from male to female and from old man to child, bodies that are more-old-than-woman, bodies less-man-than-child, bodies of old man-child.